The EPPO/OLAF compendium of national procedures: Slovenia - Hauck, Pierre; Schneider, Jan-Martin; Justus Liebig University Giessen (My University, 2024)
his Slovenian EPPO/OLAF volume contains thorough information like case law, legal sources, and relevant anti-fraud organisations. A compilation of national statutory laws relating to EPPO investigations in Slovenia is also included, highlighting the legal details that link the references in the EPPO-Regulation to the relevant national laws. The European Anti-Fraud Office and the investigative missions of its national partners in Slovenia are the focus of the second part of the volume, which deals with OLAF investigations. Assoc Prof Dr Benjamin Flander has acted as the publication’s national expert. While written in English, the volume includes footnotes that reproduce the original Slovenian legislation in the local language. Easily navigable with the help of visual symbols, it is designed as a quick reference tool for academics, students, practitioners and other interested readers.
Keywords: ddc:340; ddc:320